Assessing Assessment of Thermodynamics Concept Understanding: A Systematic Review - Maisyaroh, Delilah Nur; Sutopo; Parno (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2025)
This study presents a systematic review of scholarly articles examining the development of thermodynamics concept assessment tools in physics education from 2010 to 2025. The review aims to analyze the characteristics, scope, and quality of existing instruments while offering guidance for future improvements. Eleven assessment tools were identified and reviewed using a structured protocol aligned with PRISMA and the guidelines of Petticrew & Roberts. The findings reveal a strong reliance on multiple-choice formats and a primary focus on fundamental thermodynamics concepts, chiefly heat, temperature, and the laws of thermodynamics. However, key conceptual areas such as entropy in open systems, real gas behavior, and statistical interpretations of thermodynamic laws are often overlooked. Furthermore, although many instruments report content validation by experts, only a few provide evidence of construct validity or internal consistency. The review recommends that future thermodynamics assessments align with students’ cognitive development, maintain a balance between item depth and efficiency, and include underrepresented conceptual domains. Overall, the review advocates for the creation of more comprehensive and effective assessment tools in the field of thermodynamics.